The Effect of Clinically Therapeutic Plasma Concentrations of Lidocaine on Natural Killer Cell Cytotoxicity. (1st January 2015) - Ramirez, Maria F.; Tran, Peter; Cata, Juan P.
Abstract : Background: Natural killer (NK) cells can induce death in cancer cells. Previous studies suggest that lidocaine may decrease the function of NK cells. However, it is unknown whether lower concentrations of lidocaine, usually found in patients managed with continuous infusions, also impair the function of NK cells. We hypothesized that lidocaine at low concentrations preserves the function of NK cells. Methods: Cytotoxicity assays were performed to assess the function of NK cells treated with different concentrations of lidocaine (0.01–50 μM) against K562, THP-1, and OCI-AML3 cells. Similar experiments were repeated with neutralizing NK group 2, member D (NKG2D) receptor antibody or granzyme B inhibitor. The concentrations of interferon-γ, perforin, and granzyme B and the expression of NKG2D receptor ligands (major histocompatibility I complex antigen and UL16-binding protein) were measured by enzyme-linked immunosorbent assay or Western blot. Values of P < 0.05 were considered statistically significant. Results: In vitro, lidocaine enhanced the NK cell cytotoxicity against K562 at 0.01 and 0.1 μM ( P = 0.001) and against THP-1 ( P = 0.0013) and OCI-AML3 ( P = 0.0043) cells at all tested concentrations. This observed effect was inhibited by the addition of a granzyme B inhibitor and NKG2D receptor blocker (THP-1, P = 0.0005 and P = 0.0001; and OCI-AML3, P = 0.0862 and P = 0.0133). Lidocaine did not induce major histocompatibility I complex antigen or UL16-binding protein. Conclusions: Our findings suggest that clinically relevant concentrations of lidocaine enhance the in vitro function of NK cells via the release of lytic granules.